Implantação do módulo de simulação de procedimentos de manutenção da vida na sala de emergência no internato do Curso de Medicina - Pinto, Pérsio Campos Correia (2019)
Introduction: The medical internship is the period of medical graduation where the student receives preparation for medical practice, experiencing the daily routine of the profession to acquire professional competence. When students start this period they do not feel empowered and safe to perform any kind of procedure, even if supervised. Objective: To evaluate if the implantation of the simulated training module in advanced life support maneuvers in the program of Faculdade de Ciências Médicas e da Saúde (FCMS) - PUCSP will promote an increase in the confidence and safety of interns to perform procedures such as intubation orotracheal, cricotireoidostomy and chest drainage. Material and Methods: A cross-sectional, descriptive and quantitative study was carried out, which evaluated 50 students of the fourth grade of the medical course through a Likert questionnaire, who participated in the introduction of the simulation module at the boarding school. Results: The assessment of the practical content for performing the procedures for orotracheal intubation, cricothyroidostomy and chest drainage was considered appropriate by students in 91.5%, 22.2%, 80.8%, respectively. The hands-on training increased the chance of interns feeling safe at 6.6 times for orotracheal intubation, 17.7 times for cricothyroidostomy, and 1.4 times for chest drainage. Conclusion: The implementation of the simulated training module in advanced life support maneuvers in the program of Internship FCMS - PUCSP promoted an increase in the confidence and safety of students